The Main Development Trends of Sub-Saharan Africa Financial System - A. V. Fedorov (Финансы: теория и практика)
The financial system of sub-Saharan Africa is heavily dependent on foreign and international capital. The external debt of Sub-Saharan Africa is more than 60% of the total GDP, in some countries, that is about 95%. In the last decades, there has been an expansion of the influence of pan-African financial groups and central/national banks in the monetary policy of African states. Sub-Saharan Africa shows exponential growth in electronic mobile payments and the digital currency of central banks and crypto assets depends on distributed ledger technology. Regional financial centers have emerged, shaping the growth and development of African finance. The structure, specifics and main trends in the development of the financial system of sub-Saharan Africa are described in the context of the challenges facing the global financial system. The need for integration processes for the countries of the continent, the role of central banks and Pan-African financial institutions are substantiated. The possibility of implementing the concept of leapfrogging in the transition of the monetary and credit system of the African continent to national digital currencies and the use of distributed register technology are considered. The author considers the credit and monetary system of Sub-Saharan Africa as a place of financial innovations that can identify the development of the global financial system for decades to come.